2022
DOI: 10.3390/ijms23105710
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chemical Endocrine Disruptors and Hormone Modulators on the Endocrine System

Abstract: There is growing concern regarding the health and safety issues of endocrine-disrupting chemicals (EDCs). Long-term exposure to EDCs has alarming adverse health effects through both hormone-direct and hormone-indirect pathways. Non-chemical agents, including physical agents such as artificial light, radiation, temperature, and stress exposure, are currently poorly investigated, even though they can seriously affect the endocrine system, by modulation of hormonal action. Several mechanisms have been suggested t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 184 publications
(215 reference statements)
0
22
0
1
Order By: Relevance
“…Indeed, the activation of oxidative stress leads to an increase in in ammation triggers, which are associated with TDS. Compelling evidence from both in vivo and in vitro studies have shown that EDCs are related to alterations in testosterone biosynthesis [29,5]. However, the molecular mechanisms of declining testosterone biosynthesis caused by EDCs remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the activation of oxidative stress leads to an increase in in ammation triggers, which are associated with TDS. Compelling evidence from both in vivo and in vitro studies have shown that EDCs are related to alterations in testosterone biosynthesis [29,5]. However, the molecular mechanisms of declining testosterone biosynthesis caused by EDCs remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The age of around 50 years marks the onset of declining testosterone levels, signi cantly impacting an individual's overall quality of life [2][3][4]. Additionally, metabolic disorders and exposure to endocrine-disrupting chemicals (EDCs) are known to lower testosterone levels [5,6]. However, the precise molecular mechanism underlying the association between low testosterone and EDCs remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Both BPA and phthalates can significantly affect thyroid function [90,94]. However, both positive and negative correlations have been described between the urinary or serum levels of these classes of plasticizers and thyroid function [95][96][97].…”
Section: Plasticizersmentioning
confidence: 99%
“…In real microgravity, background radiation and loss of circadian cues are additional factors that may play a role in decreased endocrine function [55,56]. Another example is common plastics: bisphenol A and phthalates, two well-known endocrine disruptors, have been shown to alter the function and tissue of the parathyroid gland and contribute to tumor formation, hinting at effects on gene expression [57]. These plastics have been known to leach and contaminate spacecraft components [58].…”
Section: Future Researchmentioning
confidence: 99%